Model Pelatihan Mie Ikan Bandeng Bebas Duri Guna Diversifikasi Pangan Olahan Berkelanjutan bagi Anggota PKK POKJA 3 Desa Gumeng Gresik - Diah Puspitasari; Muhammad Ilyas Suwandi; Fransiskus Agustinus Christian L; Sagita Adya Atha Sary; Nur Afni Latansya (Bhumiputra: Jurnal Penelitian dan Pengabdian Masyarakat Global, 2026)
Milkfish is one of the leading fishery commodities in Gumeng Village, Gresik Regency. However, its utilization remains limited due to the presence of numerous fine bones and low product diversification. This community service aimed to improve the knowledge and skills of PKK POKJA 3 members through training on producing boneless milkfish noodles. The program employed a Participatory Action Research (PAR) approach involving observation, interviews, demonstrations, and hands-on practice. The results indicated significant improvements in participants' knowledge, technical skills, and entrepreneurial motivation. Participants successfully mastered deboning techniques, noodle production, hygienic packaging, and product labeling. The program also enhanced the economic value of milkfish while supporting local food diversification and women's empowerment. Therefore, the training model can serve as a sustainable community empowerment strategy for coastal villages with abundant fishery resources.